EXPLORING PROBLEMS PERTAINING TO GLOBAL COMPETENCE FORMATION IN FUTURE TEACHERS - Orazbayeva1, K.; Khalitova, I.; Atemkulova, N.; Sultanova, N.; Abdrakhmanov, A. (Scientific Journal of Pedagogy and Economics, 2018)
Global education is based on the concept that information about the world is of utter importance for human existence both in the society and in nature. Formation of the world view is connected with the selection of factors in different spheres of knowledge, with cognition strategy, information processing, and different mental processes such as exchange conditions. In this regard, one of the components of the global education process is of key importance, i.e., the formation of global thinking. In the selection of a global education concept, any educational institution should be oriented toward the general cognition of the environment. Correct development of the world view can support the formation of global competence of teachers. Therefore, the present study aimed to show that the formation of global competence need to be paid attention to, and methods to improve them need to be identified. Findings revealed that global competence is an important characteristic that pedagogues need to possess in the globalized world. However, to foster the same, it is first important to define the concept clearly and to then design and implement appropriate educational programs for future teachers